2007
DOI: 10.1103/physrevd.75.127701
|View full text |Cite
|
Sign up to set email alerts
|

Waves and solitons in the two-family Calogero model

Abstract: We analyze soliton solutions in the two-family Calogero model. There are two types of solutions, a onesoliton-antisoliton solution and a wave solution. It is shown that there is no finite number of solitons at finite distances in the limit when the period of wave solutions tends to infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…We should now substitute (A.26) and (A.29) in (A. 24). It is easy to see that the last term there vanishes:…”
Section: A1 Point Canonical Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We should now substitute (A.26) and (A.29) in (A. 24). It is easy to see that the last term there vanishes:…”
Section: A1 Point Canonical Transformationsmentioning
confidence: 99%
“…All this was the consequence of the invariance of the collective-field Hamiltonian of the twofamily Calogero model under an Abelian group of strong-weak-coupling dualities [8], analogous to (1.7). In [24] and [25] it was shown that a large class of solitons in the two-family Calogero model can be obtained by reducing it to the effectively one-family Calogero model.…”
Section: Introductionmentioning
confidence: 99%
“…The one-parameter solutions given in (29) coincide with corresponding solutions in Refs. [2], [7], and [13].…”
Section: Solutions Close To Constantmentioning
confidence: 99%